KLASIFIKASI DATA NASABAH KREDIT PINJAMAN MENGGUNAKAN DATA MINING DENGAN METODE K-MEANS PADA MEGA CENTRAL FINANCE: Active;Data Mining;K-Means;Passive;Repeat Order;Rapid Miner. - Limia Budiarti, Rike; Cendana, Gina (LP2M Universitas Nurdin Hamzah, 2022)
Mega Central Finance (MCF) Group is a company under CT.Corpora. The Mega Central Finance (MCF) Group company functions as a company engaged in financing and credit, located in Muara Bulian. The purpose of this study using the